PARTISIPASI MASYARAKAT DALAM PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI DESA KOTO BARU KECAMATAN KOTO BARU (2020): Pebi Julianto - Julianto, Pebi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2020)
Community Participation in a Self-Help Housing Stimulation Program (BSPS) in Koto Baru Village in Koto Baru (2020) with the problem formulation How is Community Participation in a Self-Help Housing Stimulant Assistance Program (BSPS) in Koto Baru Village in Koto Baru (2020) ?Research Objectives To determine Community Participation in a Self-Help Housing Stimulant Assistance Program (BSPS) in Koto Baru Village in Koto Baru (2020). This study uses a qualitative approach where data is obtaneid through field interviews of 9 informants who refer to the research indicators namely, (1) Stages of participation (2)Type of participation (3)Level of participation (4) Faktors that affect participation. The data obtained in the field were analyzed based on researchers’ interpretation which then triangulated the data and displayed excerpts of answers from research informants. The result of this study can be concluded that the Koto Baru Village has the right to be made a priority in the BSPS program, the community Participation is considered lacking in the implementation of the BSPS Program, the contributing factors are the lack of self-help in the form of money form government and the community is not involved in decision making, for that the authors suggest that the government directs, guides and controls the implementation of the BSPS program in the future so that it can run well.